Пайдақорлық қылмыстылығының теориялық мəселелері (Journal of actual problems of jurisprudence, 2019)
In this article are examined the general [kriminologichesaya] characteristic of crimes against the property and analysis and the estimation of state and tendencies of criminality, its causing factors.